Preparation and characterization of starch-based pH indicator films for anthocyanin release - N.H., Che Hamzah; Khairuddin, N.; Muhammad, I.I. (Rynnye Lyan Resources, 2024)
Perishable foods such as fish, chicken, and milk products lose their characteristic freshness over time, signalling the onset of deterioration. pH-sensitive smart indicator films are practical tools for quality control and delivery of visual information about the freshness of food through colour changes. In this study, Brassica oleracea (commonly known as red cabbage) and sago starch (SS) were used to synthesise pH-sensitive films plasticized with glycerol. Sago starch is cheap, abundant, and easily available whereas red cabbage is an excellent source of food colourants. Different concentrations of anthocyanin extracted from red cabbage (RCA) at 8%, 12%, and 16% (w/v) were incorporated into the starch films during fabrication using the solvent casting method. Colour analysis of the films towards food simulants (e.g., 3% acetic acid and 10% ethanol) was conducted. Furthermore, the structural and barrier properties of the films were investigated. Results showed that the addition of RCA increased the water vapour permeability (WVP) by 24% (8% RCA film), whereas the crystallinity index was reduced by 74% (16% RCA film) when compared to the control starch film. Likewise, the concentration of anthocyanins released in 3% acetic acid at room temperature was comparatively lower than the fridge temperature by 0.6% (16% RCA film). Hence, temperature plays an important role in controlling anthocyanin release from the starch matrix, although this depends on the type of food simulant. Hence, the natural pH indicator with visible colour changes is a simple, safe, and cost-effective tool for monitoring perishable foods.